2019
DOI: 10.3766/jaaa.18032
|View full text |Cite
|
Sign up to set email alerts
|

Communication between Audiologist, Patient, and Patient’s Family Members during Initial Audiology Consultation and Rehabilitation Planning Sessions: A Descriptive Review

Abstract: Communication during clinical consultations is an important factor that facilitates decision-making by patients and family members. For clinicians, these interactions are opportunities to build rapport and to facilitate appropriate decision-making.This article presents the literature review of studies focusing on communication between audiologist, patients, and their family members during initial audiology consultations and rehabilitation planning sessions.A literature review was conducted.The review included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 34 publications
(41 reference statements)
0
7
0
2
Order By: Relevance
“…The understanding of patient's needs beyond the traditional objective focus of the bio-medical model is often lacking in clinical encounters (Walseth and Schei 2011;Meyer, Hickson, Lovelock, et al 2014). This lack of holistic engagement has been reported previously, whereby audiologists dominate clinical conversations and often do not fully engage with patient concerns and preferences to facilitate shared decision-making (Dillon and Pryce 2020;Manchaiah et al 2019).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The understanding of patient's needs beyond the traditional objective focus of the bio-medical model is often lacking in clinical encounters (Walseth and Schei 2011;Meyer, Hickson, Lovelock, et al 2014). This lack of holistic engagement has been reported previously, whereby audiologists dominate clinical conversations and often do not fully engage with patient concerns and preferences to facilitate shared decision-making (Dillon and Pryce 2020;Manchaiah et al 2019).…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies indicate that audiologists have a powerful position as an expert within consultations, in keeping with the biomedical model (Southall, Gagn e, and Jennings 2010;Pryce, Hall, and Marks et al 2018). Audiologists dominate clinical conversations and often do not fully engage with patient concerns and preferences to facilitate shared decision-making, especially as technical and complex language is a barrier to patient understanding (Manchaiah et al 2019). This previous research supports the findings from this study, demonstrating that participants with SSD need good access to information, as this influences their decision-making, alongside reduction of barriers to understanding through simple language.…”
Section: Discussionmentioning
confidence: 99%
“…The authors observed a substantial amount of mitigative, vague and exaggerated language in these interactions and stress the need for training in such situations (Watermeyer et al 2020). In the same vein, a literature review of studies focusing on communication between audiologists and patients shows that audiologists did not take advantage of the opportunity to develop patient-centred communication and shared decision-making with clients (Manchaiah et al 2019).…”
Section: The Delivery Of Bad News In Speech Therapymentioning
confidence: 98%
“…In the same vein, a literature review of studies focusing on communication between audiologists and patients shows that audiologists did not take advantage of the opportunity to develop patient‐centred communication and shared decision‐making with clients (Manchaiah et al . 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Throughout the process of obtaining a case history, clinicians can build significant rapport with their patients and begin to determine the specific hearing needs of their patients. 1 In addition, this initial interaction can foster trust between the clinician and the patient. This can enhance patient care and result in improved outcomes because the patient's thoughts and opinions are valued, and the patient sees engagement from the clinician, which increases their feeling of being valued.…”
Section: The Case Historymentioning
confidence: 99%